A ‘Conditioned Emergence’ Approach to Managing Systemic Change in Sport: Insights From Golf Australia - McLeod, J; O’Boyle, I; Shilbury, D; Ferkins, L; MacIntosh, R (Informa UK Limited, 2024)
Research question: Managing systemic change within sport governing bodies is a complex challenge. This paper uses the lens of complexity theory to shed new light on the process and investigates the following question: How can the ‘conditioned emergence’ model inform the management of systemic change within sport governing bodies? Research method: Qualitative research was conducted with Golf Australia, which in 2018 moved from a federated to a unitary ‘one-management’ structure. A total of 21 semi-interviews were conducted with key stakeholders involved in the change. Findings: The study reveals that Golf Australia’s leaders faced considerable difficulty managing the change. Complexity theory is found to be a potent explanatory lens, highlighting how the organisation’s ‘deep structure’ and order-generating rules acted as a powerful constraining force. Additionally, findings show that adopting a more intentional quasi-emergent change strategy, encapsulated by the three-step ‘conditioned emergence’ model–comprising ‘conditioning’, moving to far-from-equilibrium conditions’, and ‘managing feedback processes’–could have helped overcome this constraining force and facilitate a smoother transition. Implications: This research extends the sport organisational change literature by introducing a new theoretical perspective for understanding change dynamics in sport governing bodies. It highlights the conceptual value of viewing these organisations as complex systems constrained by deep structures and rules. Furthermore, it demonstrates the utility of a quasi-emergent change approach, namely the conditioned emergence model, for effectively managing systemic change within such intricate and complex environments.
Keywords: 3504 Commercial Services; 35 Commerce, Management, Tourism and Services; 3507 Strategy, Management and Organisational Behaviour; 1504 Commercial Services